What Need is There for an Environmental Aesthetics? - Harries, Karsten (The Nordic Journal of Aesthetics, 2011)
<!–StartFragment–> What need is there for an environmental aesthetics? The answer to that question is by no means obvious. To be sure, that we need to protect our environment has become a cliché that I am just a bit wary about repeating it here – the statement hardly bears much discussion any longer. Is it not obvious that we need to make sure that all those natural resources on which we depend for our survival will continue to be available, not just to us, but to future generations? And when we think here of natural resources, we should consider them in the widest possible sense so that they include what the ancients thought of as the four elements, air, water, earth and fire. And here I invite you to think of them in their modern transformations. Even space has become an increasingly scarce resource. But if all this is indeed obvious, if the facts today speak loudly enough, it is not at all clear why we should be in need of an environmental aesthetics? What, if anything, does aesthetics have to contribute to our attempt to meet the environmental problems we face? <!–EndFragment–>